2018
DOI: 10.1002/jbio.201800255
|View full text |Cite
|
Sign up to set email alerts
|

Automated assessment of breast cancer margin in optical coherence tomography images via pretrained convolutional neural network

Abstract: The benchmark method for the evaluation of breast cancers involves microscopic testing of a hematoxylin and eosin (H&E)‐stained tissue biopsy. Resurgery is required in 20% to 30% of cases because of incomplete excision of malignant tissues. Therefore, a more accurate method is required to detect the cancer margin to avoid the risk of recurrence. In the recent years, convolutional neural networks (CNNs) has achieved excellent performance in the field of medical images diagnosis. It automatically extracts the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…This technique focuses on transferring features of a deep neural network learned on a larger dataset to a small dataset. Research has shown that transfer‐learning strategies lead to promising results when applied for small spectroscopic dataset . However, transferring features of a deep neural network which is pretrained on a dataset like ImageNet, to perform classification or regression tasks on spectroscopic data, is debatable.…”
Section: Discussion and Critical Issuesmentioning
confidence: 99%
See 4 more Smart Citations
“…This technique focuses on transferring features of a deep neural network learned on a larger dataset to a small dataset. Research has shown that transfer‐learning strategies lead to promising results when applied for small spectroscopic dataset . However, transferring features of a deep neural network which is pretrained on a dataset like ImageNet, to perform classification or regression tasks on spectroscopic data, is debatable.…”
Section: Discussion and Critical Issuesmentioning
confidence: 99%
“…Based on the two transfer learning strategies, the size of the dataset, the similarity between the datasets and the similarity between the tasks (classification or regression) involved, four major approaches can be utilized : If the new dataset is small and similar to the original dataset, then the generic features from the top layers of a pretrained deep neural network will be relevant for the new dataset and thus these generic features can be used to train an easy classifier. If the new dataset is large and similar to the original dataset, then fine‐tuning of the whole pretrained deep neural network can be performed. If the new dataset is small and different from the original dataset, then it is best to train a linear classifier (linear discriminant analysis or support vector machine) by using activations from the top and intermediate layers of a pretrained deep neural network. Previous research reported that this method works best for small spectroscopic datasets . However, for biophotonics this needs proper investigation depending on the dataset. If the new dataset is large and different from the original dataset, then it is beneficial to train a deep neural network from scratch and initialize the weights using a similar pretrained deep neural network model. …”
Section: Discussion and Critical Issuesmentioning
confidence: 99%
See 3 more Smart Citations